2000
DOI: 10.1108/01437730010318165
|View full text |Cite
|
Sign up to set email alerts
|

Testing the SMT and Belbin inventories in top management teams

Abstract: This article focuses on, examines and contrasts two managerial inventories: the Spectral management theory (SMT) and the Belbin team roles inventory. The SMT inventory is one of the only approaches that involves not only a management typology, but also learning roles as well as team assessment. The theory leads to eight such types of managerial style, measured through an analytical instrument designed to enable people to identify their personal orientations. Belbin’s inventory is focused on team roles, prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Differences in the interpretation of effect sizes are evident in the literature. For example, similar results (a correlation of 0.30) have been interpreted as providing a lack of support for convergent validity (Broucek and Randell, 1996, p. 396), while others have considered such values as indicators of convergent validity (Beck et al, 1999;Lessem and Baruch, 2000). This inconsistency has led to mixed claims about validity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the interpretation of effect sizes are evident in the literature. For example, similar results (a correlation of 0.30) have been interpreted as providing a lack of support for convergent validity (Broucek and Randell, 1996, p. 396), while others have considered such values as indicators of convergent validity (Beck et al, 1999;Lessem and Baruch, 2000). This inconsistency has led to mixed claims about validity.…”
Section: Discussionmentioning
confidence: 99%
“…These related to a potential gender bias of the instrument (Anderson and Sleap, 2004), to the prediction of team performance (Jackson, 2002; Partington and Harris, 1999), to associations between team roles and a physiological measure of brain dominance (Sommerville and Dalziel, 1998) and to relationships with the Team Management System role model (Rushmer, 1996). Eighteen studies have reported positive evidence including team roles in relation to management styles (Lessem and Baruch, 2000), to team performance (Aritzeta and Ayestaran, 2003; Senior, 1998), to cognitive styles (Aritzeta et al., 2005b) and to the exercise of power and control (Fisher et al., 2001b). A summary of empirical studies is now provided.…”
Section: The Team Role Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only team interdependence is studied as the antecedent of team behavioral integration, which leads to relatively less explanatory power of the model. Although team interdependence is one of the most important topics in team research (Barrick et al 2007), and is argued to have great value for knowledge-building in work teams (Kozlowski and Bell 2003), other factors such as team leadership, team member personality traits, and team member interpersonal skills may also contribute to team behavioral integration and ultimately promote team performance in work team settings (e.g., Lessem and Baruch 2000;Ling et al 2008;Hunt and Baruch 2003). Attention should be paid to other causal factors in future studies.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…However, subsequent investigation (Furnham et al, 1993a, b;Belbin, 1993b;Fisher et al, 1996;Broucek and Randell, 1996) of the ipsative self-perception team role inventory led to the recommendation (Broucek and Randell, 1996) that it not be used for the derivation of Belbin team role scores. Not all users of and investigators into Belbin's team role theory have been mindful of the recommendation (Arroba and Wedgwood-Oppenheim, 1994;Lessem and Baruch, 2000;Partington and Harris, 1999;Senior, 1997Senior, , 1998Senior and Swales, 1998;Shi and Tang, 1997;Watkins and Gibson-Sweet, 1997). Furthermore, questions have been raised by Broucek and Randell (1996) regarding the construct validity of the Belbin team roles, but their validation study was based on scores derived from the selfperception team role inventory.…”
mentioning
confidence: 99%